Thermal expansion behaviors of 0–3 connectivity lead-free barium zirconate titanate-Portland cement composites - Potong R. (2017)
© 2017 Elsevier Ltd and Techna Group S.r.l. New study on thermal expansion properties of 0–3 connectivity lead-free barium zirconate titanate (BZT:5%Zr)-Portland cement composites were determined in the temperature range of approximately −100 to +250 °C by dilatometer thermal expansion measurement. All the composites were found to have the three phase transitions of BZT ceramic in the cooling cycle. The physical and mechanical properties of hydration product in cement matrix were changed at elevated temperatures and the results were concluded from the thermal expansion data. When compared to the concrete structure, the thermal expansion coefficient value of the 0–3 composites with ≈ 30–70% of barium zirconate titanate ceramic content can be matched with concrete. The theoretical equations of models were applied for the calculation with the thermal expansion coefficient and the results were found to fit closest to that of the Dougill's model.